Wrongdoing and whistleblowing in health care - Pohjanoksa J; Stolt M; Suhonen R; Leino-Kilpi H (Blackwell Scientific Publications, 2022)
AIM(S):
To describe healthcare professionals' experiences of observed wrongdoing and potential whistleblowing acts regarding it. The main goal is to strengthen the whistleblowing process described based on the existing literature and to make it more visible for future research.
DESIGN:
A descriptive cross-sectional survey.
METHODS:
Data were collected between 26 June 2015-17 July 2015 from the Finnish trade union's membership register, electronically using one open question. A total of 226 healthcare professionals participated providing written narratives, which were analysed using inductive content analysis.
FINDINGS:
The whistleblowing process in health care was strengthened, identifying the content of observed wrongdoings and whistleblowing acts regarding them. Three themes were identified: wrongdoing related to patients, healthcare professionals, and healthcare managers. Whistleblowing acts were performed internally, externally, or left undone. Three main paths: internal, external, and no whistleblowing, between an observation of wrongdoing and whistleblowing act were identified.
CONCLUSION:
The whistleblowing process should be further developed and ethically effective programmes and interventions should be developed for increasing whistleblowing and preventing wrongdoing in health care.